Interior planning and design of an appliance store - Medina, Rachelle F.
This reseacrh concerned the planning and design of proposed appliance showroom for Mr. Ricardo Nuguid. The objective of this research, as to be restated later, was to find creative possibilities in the design of retail stores; specifically hard goods specialty stores, through the design development of this case study. Throughout the development of this research, several research methods were conducted; interviews with the client, participation in this actual planning of the store space, accumulation of useful data from related written sources. With the application of the above research methods, the researcher arrived at this statement: Through the designer's creative and considerate proposals in space planning and decorative design, small areas for commercial purposes can be maximized spatially and aesthetically. Development of the case study's plans and design supported this statement.